Storage Studies on Kattha - Beri, H. M.; Dobhal, N. P. (Indian Forester, 1982)
Storage studies on two sample of kattha having 67.5 and 70.8 per cent of catechin were made under different storage conditions for a period of one year. The studies indicate that diffused light does not affect the colour or composition of dry samples of kattha having lesser amounts of cutch.